THE STRENGTH RESEARCH OF THE COUPLER PARTS DURING THE EXPLOITATION DOWNLOADING - Kuzmin, O. B.; Kossov, V. S.; Protopopov, O. L.; Krasiukov, M. F.; Bunin, B. B.; Ohanian, E. S. (Science and Transport Progress, 2007)
One of the most frequent failures of the coupling mechanism СА-3 is the coupler body damage. In this article the investigation of the stress-strain state of the coupling mechanism under service loads is fulfilled, the areas are detected were formation and growth of the fatigue cracks is possible and assessments of the coupler durability considering its survivability are obtained.